2017
DOI: 10.1016/j.ufug.2017.05.010
|View full text |Cite
|
Sign up to set email alerts
|

The effects of “greening” urban areas on the perceptions of tranquillity

Abstract: Tranquil environments can provide relief from stresses of everyday of life and can be considered restorative environments. This paper considers the effects of "greening" urban environments to enhance tranqui llity and ultimately well-being and health benefits. A number of studies have been conducted at the Bradford Centre for Sustainable Environments at the University of Bradford which have examined the effects of natural features on ratings of tranquillity. These include quantifying the effects of the percent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 16 publications
1
22
0
Order By: Relevance
“…Besides, all the visit motivations showed positive relationships with visual landscape preference. As pointed out by other researchers, tranquillity could be predicted by natural and contextual features (Watts, 2017;Watts et al, 2013). It is also verified by many researchers the existence of audio-visual interaction (Hong and Jeon, 2014;Pheasant et al, 2010).…”
Section: Effects Of Visit Motivations On Overall Soundscape Preferencesupporting
confidence: 58%
See 1 more Smart Citation
“…Besides, all the visit motivations showed positive relationships with visual landscape preference. As pointed out by other researchers, tranquillity could be predicted by natural and contextual features (Watts, 2017;Watts et al, 2013). It is also verified by many researchers the existence of audio-visual interaction (Hong and Jeon, 2014;Pheasant et al, 2010).…”
Section: Effects Of Visit Motivations On Overall Soundscape Preferencesupporting
confidence: 58%
“…The focuses were on either the effects of vegetation on physical reduction of noise, such as traffic noise reduction by single plants, green walls, and hedges (Fang and Ling, 2003;Horoshenkov et al, 2013;Van Renterghem et al, 2014;Wong et al, 2010;Yamada, 2006), or by land use parameters emphasizing on green spaces (Margaritis and Kang, 2016), or the psychological noise attenuation (Dzhambov and Dimitrova, 2014;Dzhambov and Dimitrova, 2015). In practical aspect, tranquillity rating prediction tool has been proposed for urban green areas (Watts et al, 2013), and was further applied to predict greening effect on tranquillity in city squares (Watts, 2017). Soundscape-based forest planning for recreational and therapeutic activities was also proposed (Yamada, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…These studies indicate that the tool can be used with some confidence. The effects on predicted perceived tranquillity of town squares, city parks alongside major roads and residential roads and gardens under varying conditions have all been examined [10]. This illustrates the approach that can be taken by concerned groups such as planners, environmentalists, civic leader and citizens in order to determine changes in tranquillity levels brought about by various interventions both positive and negative.…”
Section: Discussionmentioning
confidence: 99%
“…For example, for a TR value of 5.0 nearly 50% of visitors report that they are "more relaxed" after visiting the park while at a value of 8 approximately 80% report being "more relaxed". These results have been used to validate the following category limits for TR defined previously [7]: <5 unacceptable 5.0 -5.9 just acceptable 6.0 -6.9 fairly good 7.0 -7.9 good ≥ 8.0 excellent A previous study [10] employed TRAPT to gauge the benefits of "greening" urban areas. In this paper we look at a means of encouraging people to visit existing green and tranquil spaces.…”
Section: Introductionmentioning
confidence: 99%
“…It was also shown that this classification influences the effect of visual context on evaluation of the sonic environment and the strength of the contribution of the sonic environment to the overall appreciation of an environment [ 30 ]. The third factor considered in this study is related to personal expectations and connections to “greenery” as an environmental mediator; that is a (positive) preconception people might have about the potential of natural features to compensate for negative effects of noise and air pollution [ 12 , 31 ].…”
Section: Introductionmentioning
confidence: 99%